PENINGKATAN KETERAMPILAN MENULIS PARAGRAF DESKRIPTIF PADA SISWA KELAS X4 SMA NEGERI 3 BULUKUMBA - Suhartina Suhartina (Al-Ishlah: Jurnal Pendidikan Islam, 2017)
This classroom action research aims to improve students' writing skill of class X4 SMA Negeri 3 Bulukumba. The subjects of the study were the students of class X SMA Negeri 3 Bulukumba as much as 42 people. The object of research is the technique of direct object and peer editing, as well as the skill of writing the description. The action is done in two cycles. Each cycle consists of four stages, namely planning, implementation, observation / evaluation, and reflection. The research data is the data writing skill descriptions collected through the guidelines of writing descriptions and observation skills. Data were analyzed descriptively quantitative. The result of research shows that firstly, the process of learning with direct object technique that can improve the writing skill of descriptive paragraph of X-4 students of SMA Negeri 3 Bulukumba is by applying direct object technique in cycle I through planning, implementation, evaluation and reflection phase. In the first cycle of learning to write a descriptive paragraph is considered less than the maximum so that learning is continued into cycle II by designing the learning using direct object engineering and peer editing techniques. Second, the learning result of descriptive paragraph writing skill with direct object and peer editing technique has increased the average score of students who in cycle I only 81.3 increased to 88.1. In addition, there is also a significant change in attitude in students.